Increasing firms’ motivation to train low-skilled youth : a factorial survey experiment - Wenzelmann, Felix [Verfasser]; Risius, Paula [Verfasser]; De Grip, Andries [Verfasser] (Bundesinstitut für Berufsbildung, 2024)
"The German system of apprenticeship training is often claimed as an important driver for the good integration of youth in the labour market. Nonetheless, a steady share of 13% of school graduates who would like to start an apprenticeship are unable to find a training position. In this paper, we use a factorial survey experiment, which we included, in a large-scale firm survey on apprenticeship training to analyse whether a financial or a non-financial bonus scheme could increase firms´ willingness to train low-skilled youth. In the experiment, we ask firms to rate the probability of providing a training position to hypothetical applicants that vary on cognitive and social skills and the possibility of receiving financial or non-financial support. We find that both applicants’ cognitive and non-cognitive skills are highly important for a firm’s decision to offer low-skilled applicants a training position. High non-cognitive skills can compensate for low cognitive skills. However, neither financial nor non-financial support can compensate for a low cognitive or non-cognitive skill level, as the effects of both support measures are rather weak." (BIBB-Autorenreferat)
Keywords: G 1.3.1.1 Ausbildungsstellenmarkt; S 5.3 Personalentwicklung; P 2.2 An- und Ungelernte; S 4 Kosten & Finanzierung; P 1.7 Benachteiligte; 370; Betriebliche Berufsausbildung; Ausbildungsbereitschaft; Geringqualifizierter; Förderprogramm; Benachteiligtenförderung; Kognitive Fähigkeit; Finanzierung; Ausbildungschance; Faktorieller Survey; Personalgewinnung